PENGEMBANGAN ARBORETUM TANAMAN TARUPREMANA UNTUK MENINGKATKAN DAYA TARIK WISATA DI DESA TARO KECAMATAN TEGALLALANG KABUPATEN GIANYAR - Singarsa, I.D.P.; Sardiana, I.K.; Windia, W.P.; Dinata, K.K. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana Mengabdi, 2018)
The Community service activities aimed is to develop arboretum of taru Premana plant to increase the attractiveness of tourist village of Taro, District Tegallalang, Gianyar. The method applied in this community empowerment, among others: (1) Coordination and participatory communication with village leaders and villagers taro to formulate a program from the planning, operational and evaluation; (2) Counseling on the importance of the development of the arboretum taru premana and travel awareness groups to manage the tourism potential of the village; (3) planting taru premana accordance trihita karana philosophy; (4) Assistance is meeting regularly and sustainably among companion with target communities. The results showed that the arboretum “taru premana” plant development activities have been going well. The number of plants taru Premana that can be planted as many as 1,000 trees, consists of nine types, ie 400 trees of coconut daksina and 600 trees of the wood are sandalwood, nagasari, nutmeg, cempaka, mundeh, kwanitan, Rijasa, and majegau. People respond positively to community service activities are carried out as in accordance with the potential and needs of the community.